2020
DOI: 10.3389/fphar.2020.567582
|View full text |Cite|
|
Sign up to set email alerts
|

Functioning of Long Noncoding RNAs Expressed in Macrophage in the Development of Atherosclerosis

Abstract: Chronic inflammation is part of the pathological process during atherosclerosis (AS). Due to the abundance of monocytes/macrophages within the arterial plaque, monocytes/macrophages have become a critical cellular target in AS studies. In recent decades, a number of long noncoding RNAs (lncRNAs) have been found to exert regulatory roles on the macrophage metabolism and macrophage plasticity, consequently promoting or suppressing atherosclerotic inflammation. In this review, we provide a comprehensive overview … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…Previous studies have revealed the potential atherogenic role of GAS5 through its upregulation in endothelial cells and macrophages following ox-LDL stimulation [ 13 , 36 ]. GAS5 knockdown suppressed apoptosis, inflammation, and cholesterol efflux in ox-LDL treated THP-1 cells [ 16 , 17 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed the potential atherogenic role of GAS5 through its upregulation in endothelial cells and macrophages following ox-LDL stimulation [ 13 , 36 ]. GAS5 knockdown suppressed apoptosis, inflammation, and cholesterol efflux in ox-LDL treated THP-1 cells [ 16 , 17 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced phagocytosis improves lipid uptake and foam cell formation, enables lesion formation, which is protective in the early stage of atherosclerosis [ 31 ]. In advanced atherosclerosis, incomplete clearance and defective phagocytosis give rise to necrotic cores, which might contribute to plaque instability and plaque rupture [ 44 ]. Thus, further in vivo studies are needed to determine whether miR-185-5p plays diverse role in different stages of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA-Mirt2 inhibits the NF-κB and MAPK pathways activation and limits the production of pro-in ammatory cytokines through negative feedback 38 . In addition, lncRNAs can participate in in ammatory progression by regulating macrophage oxidative stress and metabolism 39,40 . Our study found that LINC01126 silencing signi cantly reduced expression of proin ammatory cytokines in LPS-induced HGFs, particularly IL-6.…”
Section: Discussionmentioning
confidence: 99%